Relationship between Working Capital Elements and Company Profitability - Arifani, Arifani (Advances: Jurnal Ekonomi & Bisnis, 2023)
Purpose: This study examines the effect of working capital elements, including cash turnover, receivables turnover, inventory turnover, and current liabilities turnover, on profitability (ROA) in food and beverage companies listed on the Indonesia Stock Exchange (IDX). The research focuses on understanding whether efficient management of these working capital components influences the companies' profitability. Research Design and Methodology: This study's population includes 16 food and beverage companies listed on the IDX from 2014 to 2016. Using purposive sampling, 10 companies were selected as the final sample. This research relies on quantitative data derived from company financial statements as secondary data. The analysis includes classical assumption tests (normality, autocorrelation, and multicollinearity) and hypothesis testing using partial (t-test), simultaneous (F-test), and determination coefficient tests to assess the influence of the independent variables on profitability. Findings and Discussion: The study finds that cash and inventory turnover has a positive but insignificant effect on profitability (ROA), indicating that efficient management of these components does not substantially increase profitability. Meanwhile, receivables and current liabilities turnover shows a negative but insignificant effect on ROA, suggesting these components do not significantly influence profitability. Implications: The results imply that while working capital elements affect operational efficiency, they do not significantly drive profitability. Thus, companies should focus on managing working capital and other strategic factors to improve financial performance.